2003
DOI: 10.1001/archneur.60.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of Cognitive Impairment With No Dementia

Abstract: Persons with CIND were more likely to have a negative outcome than persons with NCI during a 5-year interval. This was true across etiologic subcategories and suggests that the use of specific diagnostic criteria sets does not improve our identification of those who develop dementia compared with a broader, more inclusive approach. More factors contributed to the prediction of all forms of dementia than to AD, but the most accurate prediction was for those who remained dementia free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(148 citation statements)
references
References 21 publications
13
130
0
5
Order By: Relevance
“…We observed a conversion rate from CIND to dementia of 12% per year, similar to the rates observed in prior studies 14 . We did not observe similar associations for conversion from aMCI to dementia.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a conversion rate from CIND to dementia of 12% per year, similar to the rates observed in prior studies 14 . We did not observe similar associations for conversion from aMCI to dementia.…”
Section: Discussionsupporting
confidence: 90%
“…The risk factor profile for cognitive impairment without dementia differed from that for dementia, and incident CVD was associated with the former but not the latter. Cognitive impairment without dementia, as defined in the present study, is a broad classification [41] with a high prevalence in diabetes [42]. Mild cognitive impairment is a more restrictive category with a high rate of transition to dementia, but it has recently been shown that the subgroup of mild cognitive impairment associated with CVD is less likely to progress to dementia [43].…”
Section: Discussionmentioning
confidence: 61%
“…Mild cognitive decline is observed in about 25% of the population aged 65 or over (1) and, although this status may be an expression of normal physiological aging (2), it is also the typical presentation of the early phases of degenerative dementia (3). Epidemiological studies have linked cognitive impairment to a higher risk of dementia, institutionalization and mortality (4).…”
Section: Introductionmentioning
confidence: 99%